Re-evaluation of the Activity of Some Antibacterial Drugs Against Clinical Isolates of Staphylococcus Aureus in Al_Najaf Al_Ashref Governorate. - Saif Jabbar Yasir; Saad B. Nashtar; Adel H. Sheeh (Kufa Journal for Nursing Sciences)
Background: Staphylococcus aurous one of the most common pathogen that cause a wide range of infection started by simple skin infection and end by septicemias and high possibility of death.